IMPLEMENTASI METODE PREFERENCE SELECTION INDEX (PSI) DALAM PEREKRUTAN MITRA KURIR J&T: IMPLEMENTATION OF THE PREFERENCE SELECTION INDEX (PSI) METHOD IN RECRUITING J&T COURIER PARTNERS - Alfisyahrin; Zara Yunizar; Hafizh Al Kautsar Aidilof (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
The recruitment process for courier partners is an important aspect in maintaining the quality of delivery services in logistics companies such as J&T Express. Selecting the right candidate requires an objective and systematic method so that the decisions taken can be accounted for. This study aims to apply the Preference Selection Index (PSI) method to assist the decision-making process in the selection of courier partners. The PSI method is used to evaluate and rank prospective partners based on a number of criteria, including work experience, communication skills, problem-solving skills, discipline, and teamwork skills. This research was conducted at J&T Bireun. The analysis process was carried out through the stages of normalization, calculation of preference deviations, and determination of the final preference index value. The data used amounted to 10 employee candidates with the highest ranking results, namely Ridwan with a score of 8.6, Zikra with a score of 8.55 and Syakir with a score of 8.55. The results of the study show that the PSI method is able to provide objective and efficient selection results, and makes it easier for companies to determine the best courier partner candidates. Thus, this method is worthy of consideration as a tool in a multi-criteria-based recruitment system in the logistics industry.The courier partner recruitment process is one of the important aspects of maintaining the quality of delivery services in logistics companies such as J&T Express. The selection of appropriate candidates requires objective and systematic methods for the decision to be taken accountable. The Preference Selection Index (PSI) method to assist the decision-making process on the selection of courier partners. PSI method is used to evaluate and rank prospective partners based on a number of criteria, including work experience, communication skills, problem solving capabilities, discipline, and teamwork capabilities. This study was conducted on J&T Bireuen. The analysis process is performed through the normalization stage, preference deviation calculation, and the determination of the final preference index value. The data sample used amounted to 10 candidates with the highest ranking results, namely Ridwan with value (8.6), Zikra with value (8.55), and Syakir with value (8.55). Research results in the application of PSI methods for labor selection in the logistics sector, especially in the operational position of courier partners indicate that it is able to provide objective and efficient selection results, and facilitate the company in determining the best courier partner candidates. Thus, this method is worth considering as an alterative tool in a proof-criterion-based recruitment decision support system in the logistics industry.